Assessing the Current Level of Transport Education and the Impact on Safety Compliance Among Road Operators in Ogbomoso, Oyo State - R, Aworemi J.; B, Ayantoyinbo B.; M, Gegeleso O.; A, Ige L. (International Journal of Humanities, Education, and Social Sciences, 2025)
The road transportation sector in the Ogbomoso area of Oyo State plays a critical role in facilitating the movement of people, goods, and services, thereby supporting local economic activities. Despite its importance, there remains limited understanding and implementation of transport education, safety compliance, and regulatory frameworks among road transport operators in the region. This study seeks to assess the level of transport education among road users and identify the challenges faced by operators in accessing such education. A survey research design was adopted, utilizing structured questionnaires and interviews to collect data. The study population comprised 310 individuals, including 210 public motor park drivers (based on 2024 park management records), 30 administrative staff and drivers from private transport companies such as Tribel Global Motors (TGM) and MST Executive Transport Service, and 70 officials from the Federal Road Safety Corps (FRSC), Ogbomoso Area Command. A sample of 175 respondents was selected using the Taro Yamane formula. Data were analyzed using descriptive statistics (percentage counts) and inferential analysis through multiple regression. Findings revealed that while slightly more than half of the respondents had received some form of transport education, significant gaps persist, particularly in formal training and safety regulation awareness. The study concludes that the overall level of transport education among road operators in Ogbomoso remains low, underscoring the urgent need for enhanced educational campaigns and training programs aimed at promoting safety compliance and regulatory adherence. It recommends coordinated efforts among government agencies, transport unions, and private stakeholders to improve access to structured driver education and regulatory awareness.